Official Eclipse 3.0 FAQs - Arthorne, John (Eclipse series., 2004)
"I had a question about how to use a new Eclipse 3.0 feature, job scheduling, so I thought I would try out this book. I immediately found the answer with a concise explanation. Cool!" --Erich Gamma Official Eclipse 3.0 FAQs is the convenient source for answers to your most crucial questions about writing Eclipse plug-ins. Whether you're creating simple extensions for personal use or commercial Eclipse-based applications, you'll find hundreds of concise solutions here--including many that aren't answered anywhere else. John Arthorne and Chris Laffra have worked with Eclipse technology since the very beginning; both are active members of the Eclipse development community and frequently answer questions on Eclipse newsgroups and mailing lists. Here, they cover an extraordinary range of topics, from workspace management to documentation, SWT to JFace, JDT to natural language support. Many FAQs include code samples and references to other information, making the book an invaluable desk reference for anyone working with Eclipse. Just a few of the 350+ questions answered here... How do I upgrade Eclipse? Page 29 What is new in Eclipse 3.0? Page 34 How can I add my views and actions to an existing perspective? Page 187 How do I set up a Java project to share in a repository? Page 58 How do I declare my own extension point? Page 74 How do I display a Web page in SWT? Page 141 How do I support multiple natural languages in my plug-in messages? Page 253 How do I save settings for a dialog or wizard? Page 166 How do I provide syntax coloring in an editor? Page 269 How do I hook into global actions, such as Copy and Delete? Page 225 How do I create a Rich Client application? Page 241 What is the purpose of activities? Page 229 How do I create and examine an AST? Page 369.